A PE / PET composite fiber material and preparation method thereof
By grafting modified polyethylene and polyacrylamide in PE/PET composite fiber materials with terminal amino polyether graft modified polyethylene and polyacrylamide, combined with aminosilane to modify porous silica, the problems of insufficient water absorption, breathability and mechanical properties of composite fiber materials are solved, and efficient moisture absorption, wet conduction and quick drying effects are achieved.
Patent Information
- Application Number
- CN202410945274.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-15
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-07-15
AI Technical Summary
The water absorption, breathability and mechanical properties of existing PE/PET leather-core composite fiber materials cannot meet the quality improvement needs of nonwoven fabrics.
By using end amino polyether grafted modified polyethylene as the main raw material of the cortex and using polyacrylamide grafted PET as the main raw material of the core layer, amino and amide bonds are introduced to improve the moisture absorption effect and mechanical properties of the fibers. At the same time, aminosilane modified porous silica is added to the cortex to improve moisture conduction performance.
It realizes good mechanical strength, hygroscopicity and breathability of PE/PET composite fiber materials, improves the quick drying effect of non-woven fabrics, and meets the quality improvement needs of non-woven fabrics.
Smart Images

Figure BDA0004945441870000091 
Figure BDA0004945441870000101
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of preparation of polymer materials, and in particular to a PE / PET composite fiber material and a preparation method thereof. Background Art
[0002] Polyester fiber, commonly known as "polyester", is a synthetic fiber obtained by spinning polyester formed by the polycondensation of organic dibasic acid and diol, referred to as PET fiber, which belongs to a polymer compound; PE fiber is the abbreviation of ultra-molecular polyethylene fiber. The core-skin composite short fiber with PE as the skin layer and polyester PET as the core layer is a kind of non-woven fabric raw material. It is made of PE and PET as the main raw materials. The fabric is soft and comfortable, and is widely used in the production of diapers, underwear, sportswear, etc.
[0003] However, the resin used in the PE / PET skin-core structure has poor hydrophilicity, resulting in poor moisture absorption and poor air permeability of the fabric made from the finished fiber. At the same time, the difference in the resin structure of PE and PET leads to poor bonding between the skin and the core, which easily causes interface separation and affects the mechanical properties of the fiber. Conventional polyester PET fibers that have undergone surface hydrophilic treatment can no longer meet the processing requirements of highly hydrophilic non-woven fabrics. Therefore, improving the water absorption, air permeability and mechanical properties of PE / PET skin-core composite fibers is of great significance for further improving the application prospects of PE / PET skin-core composite fibers in non-woven fabrics and other fields. Summary of the invention
[0004] In view of the problem that the water absorption, air permeability and mechanical properties of sheath-core composite fibers cannot meet the quality improvement requirements of non-woven fabrics, the present application provides a PE / PET composite fiber material and a preparation method thereof.
[0005] In the first aspect, the present application provides a PE / PET composite fiber material, adopting the following technical scheme: a PE / PET sheath-core composite fiber material, characterized in that it includes a sheath layer and a core layer, the sheath layer raw material includes the following components in parts by mass: 20-40 parts of modified PE resin, 2-8 parts of toughening agent, and 1-4 parts of antioxidant; the core layer raw material includes the following components in parts by mass: 30-65 parts of modified PET resin; wherein the modified PE resin is amino-terminated polyether grafted polyethylene; the modified PET resin is polyacrylamide grafted PET.
[0006] By adopting the above technical scheme, the surface treatment process of conventional polyester PET resin and PE resin is relatively simple, so that the continuous hydrophilicity, air permeability and mechanical properties of the fiber cannot meet the use requirements. The inventor uses terminal amino polyether grafting to modify polyethylene as the main raw material of the cortex, and uses polyacrylamide grafting to PET as the main raw material of the core layer. More hydrophilic groups are embedded in the PE macromolecules. Terminal amino polyether is an amine compound with a polyether structure, which has certain water solubility and hydrophilicity, and the polyacrylamide molecular chain contains amide groups and amino groups, which makes the modified PET resin very hydrophilic. The modification is performed at the same time so that both the cortex and the core layer have good moisture absorption effects. Both modification methods introduce amino groups and amide bonds into the fiber resin, so that similar structures exist in the resin structure, the interface compatibility of the cortex and the core layer is improved, the strength of the composite fiber is improved, and good mechanical strength is achieved. In addition, different hydrophilic grafting modification methods achieve different moisture absorption capacities of the skin-core structure, and there is a moisture absorption difference, which can further accelerate the moisture absorption and moisture conduction of the fiber and improve the quick-drying effect of the non-woven fabric.
[0007] In a specific embodiment, the skin layer raw material further comprises 3-9 parts of aminosilane-modified porous silica.
[0008] Porous silica has good capillary moisture conduction. When added to the cortex, it can quickly absorb sweat and conduct the sweat out through the moisture conduction to achieve a dry and breathable effect. Aminosilane modification can further promote the compatibility and binding stability of porous silica in PE resin and improve the moisture conduction effect. The amino groups grafted on the surface of silica and the amino groups in modified PE and modified PET can strengthen the bonding force based on hydrogen bonding, thereby further enhancing the bonding force between the cortex and the core layer and improving the mechanical properties of the fiber.
[0009] In a specific embodiment, the preparation of amino-terminated polyether grafted polyethylene includes the following steps: plasma treating polyethylene; adding the treated polyethylene and amino-terminated polyether to DMF solution, reacting at 90-95°C for 2-4h, removing the solvent and drying to obtain amino-terminated polyether grafted polyethylene.
[0010] Polyethylene is chemically inert and cannot be directly chemically grafted. Conventional high-temperature activation conditions are harsh and costly. The present application forms multiple active groups such as carboxyl and hydroxyl groups on the polyethylene resin through plasma treatment to achieve grafting of hydrophilic segments, thereby improving the hygroscopicity of the cortex. On the other hand, the plasma treatment etches the polyethylene surface to make it rough. After the fabric is made, sweat is discharged through the etched channels on the surface of the cortex. At the same time, part of the sweat can also be discharged or introduced into the core layer through the moisture conduction effect without staying in the channel. The above-mentioned combined effect leads to the final fabric being able to achieve quick drying and good breathability.
[0011] In a specific embodiment, the core layer material further comprises 1-3 parts of a hygroscopic filler, and the hygroscopic filler is one or more of diatomaceous earth, sepiolite, and perlite.
[0012] Adding fillers with hygroscopic effect into the core layer can further improve the hygroscopicity of the core layer. At the same time, the hygroscopic filler has a certain water storage capacity. The sweat in the core layer can be absorbed by the core layer while being discharged through the cortex, thereby achieving a better quick-drying effect.
[0013] In a specific embodiment, the preparation of the polyacrylamide grafted PET includes the following steps: carboxylation of PET resin; adding the carboxylated PET resin and polyacrylamide to DMF solution, reacting at 85-95°C for 2-4h, removing the solvent and drying to obtain polyacrylamide grafted modified PET.
[0014] Carboxylation of PET resin: immerse the PET resin in 0.5% sodium hydroxide acetonitrile solution, react at room temperature 25°C for 15 hours, wash with ultrapure water and dry, then immerse in 5% potassium permanganate sulfuric acid solution (sulfuric acid concentration 0.5 mol / L), react at 65°C for 1 hour, wash with ultrapure water and dry to obtain carboxylated PET resin.
[0015] Carboxylated PET resin and polyacrylamide were added into DMF solution, reacted at 90°C for 4 hours, and polyacrylamide grafted modified PET was obtained after removing the solvent and drying.
[0016] On the one hand, conventional carboxylation of PET is performed first to improve the hydrophilicity of PET resin. On the other hand, the grafting of polyacrylamide provides more active sites and increases the grafting rate, thereby improving the hydrophilicity and hygroscopicity of the modified PET resin.
[0017] In a specific embodiment, the mass ratio of the aminosilane-modified porous silica to the hygroscopic filler is 3:1.
[0018] The inventors tend to improve the fiber's moisture absorption, air permeability, and quick-drying effects through the moisture absorption effect of the cortex and core layer, the moisture conduction function, and the water storage capacity of the core layer. At the same time, the inventors found through experiments that when the mass ratio of aminosilane-modified porous silica in the cortex and the moisture-absorbing filler in the core layer is 3:1, the moisture absorption and air permeability are the best. This may be because the adjustment of the content of the two achieves a good synergy of moisture absorption, moisture conduction, and water storage, allowing the fiber to achieve the best quick-drying effect.
[0019] In a specific embodiment, the toughening agent is acrylonitrile-butadiene-styrene copolymer; and the antioxidant is hydroquinone.
[0020] In a second aspect, the present application provides a method for preparing a PE / PET composite fiber material, using the following technical solution: A method for preparing a PE / PET composite fiber material, comprising the following steps:
[0021] The modified PE resin, toughening agent, antioxidant, etc. are mixed in proportion, stirred at a temperature of 76-84°C for 55-60 minutes to obtain a skin layer mixture for use; the modified PET resin, etc. are stirred at a temperature of 85-95°C for 55-60 minutes to obtain a core layer mixture; subsequently, the skin layer mixture and the core layer mixture are added to a spinning machine respectively, melted, co-extruded, spun, water-cooled, drawn, dried, and cut to obtain a PE / PET skin-core composite fiber material.
[0022] In a specific embodiment, the melting temperature is 176-190°C, and the melting time is 50-60 minutes.
[0023] In summary, this application has the following beneficial effects:
[0024] 1. The surface treatment process of conventional polyester PET resin and PE resin is relatively simple, which makes the continuous hydrophilicity, air permeability and mechanical properties of the fiber unable to meet the use requirements. The inventor uses terminal amino polyether grafting to modify polyethylene as the main raw material of the cortex, and uses polyacrylamide grafting to PET as the main raw material of the core layer. More hydrophilic groups are embedded in the PE macromolecules. Terminal amino polyether is an amine compound with a polyether structure, which has certain water solubility and hydrophilicity, and the polyacrylamide molecular chain contains amide and amino groups, which makes the modified PET resin highly hydrophilic. The modification is performed at the same time so that both the cortex and the core layer have good moisture absorption effects. Both modification methods introduce amino and amide bonds into the fiber resin, so that similar structures exist in the resin structure, which improves the interface compatibility of the cortex and the core layer, improves the strength of the composite fiber, and achieves good mechanical strength. In addition, different hydrophilic grafting modification methods achieve different moisture absorption capacities of the skin-core structure, and there is a moisture absorption difference, which can further accelerate the moisture absorption and moisture conduction of the fiber and improve the quick-drying effect of the non-woven fabric.
[0025] 2. Porous silica Porous silica has good capillary moisture conduction. When added to the cortex, it can quickly absorb sweat and conduct the sweat out through the moisture conduction to achieve a dry and breathable effect. Aminosilane modification can further promote the compatibility and binding stability of porous silica in PE resin and improve the moisture conduction effect. The amino groups grafted on the surface of silica and the amino groups in modified PE and modified PET can strengthen the bonding force based on hydrogen bonding, thereby further enhancing the bonding force between the cortex and the core layer and improving the mechanical properties of the fiber.
[0026] 3. The moisture absorption, air permeability and quick-drying effects of the fiber are improved through the moisture absorption effect of the cortex and core layer, the moisture conduction function and the water storage capacity of the core layer. At the same time, the inventors found through experiments that when the mass ratio of aminosilane-modified porous silica in the cortex and the moisture-absorbing filler in the core layer is 3:1, the moisture absorption and air permeability are the best. This may be because the adjustment of the content of the two achieves a good synergy of moisture absorption, moisture conduction and water storage, so that the fiber can achieve the best quick-drying effect. DETAILED DESCRIPTION
[0027] The present application is further described in detail below with reference to the embodiments.
[0028] Some of the raw materials used in the preparation examples and embodiments: aminosilane modified porous silica 2-5nm: purchased from Beijing Zhongke Keyou Nanotechnology Co., Ltd.; terminal amino polyether is trimethylolpropane tripropylene glycol ether purchased from Wuhan Kamik Technology Co., Ltd.; polyacrylamide was purchased from Wuxi Lanbo Chemical Co., Ltd.; acrylonitrile-butadiene-styrene copolymer model: GP-22; hydroquinone was purchased from Wuxi Jingke Chemical Co., Ltd.; PET resin brand: 4410G3; PE resin brand: M2750; diatomaceous earth model: hx-1.
[0029] The raw materials used in the examples and comparative examples that are not otherwise specified are all conventional products that can be purchased from the market.
[0030] Preparation Example
[0031] Preparation of Amino-terminated Polyether Grafted Polyethylene
[0032] Preparation Example 1
[0033] The polyethylene was plasma treated, the plasma gas was high-purity oxygen, the volume flow rate was 0.01 L / min, the ionization power was set to 200 W, and the treatment time was 2 min; then 50 g of the treated polyethylene and 16 g of amino-terminated polyether were added to 300 mL of DMF solution, reacted at 90° C. for 4 h, the solvent was removed, and the amino-terminated polyether grafted polyethylene was obtained after drying at 60° C.
[0034] Preparation Example 2
[0035] The polyethylene was plasma treated, the plasma gas was high-purity oxygen, the volume flow rate was 0.01 L / min, the ionization power was set to 200 W, and the treatment time was 2 min; then 50 g of the treated polyethylene and 16 g of amino-terminated polyether were added to 300 mL of DMF solution, reacted at 95 ° C for 2 h, the solvent was removed, and the amino-terminated polyether grafted polyethylene was obtained after drying at 60 ° C.
[0036] Preparation of polyacrylamide grafted PET
[0037] Preparation Example 3
[0038] Carboxylation treatment of PET resin: immerse the PET resin in 0.5% sodium hydroxide acetonitrile solution, react at room temperature 25°C for 15 hours, wash with ultrapure water and dry, then immerse in 5% potassium permanganate sulfuric acid solution (sulfuric acid concentration 0.5 mol / L), react at 65°C for 1 hour, wash with ultrapure water and dry to obtain carboxylated PET resin; add 80g of carboxylated PET resin and 26g of polyacrylamide into 500mL DMF solution, react at 90°C for 4 hours, remove the solvent, and dry at 60°C to obtain polyacrylamide grafted modified PET.
[0039] Preparation Example 4
[0040] Carboxylation treatment of PET resin: immerse the PET resin in 0.5% sodium hydroxide acetonitrile solution, react at room temperature 25°C for 15 hours, wash with ultrapure water and dry, then immerse in 5% potassium permanganate sulfuric acid solution (sulfuric acid concentration 0.5 mol / L), react at 65°C for 1 hour, wash with ultrapure water and dry to obtain carboxylated PET resin; add 80g of carboxylated PET resin and 26g of polyacrylamide into 500mL DMF solution, react at 85°C for 4 hours, remove the solvent, and dry at 60°C to obtain polyacrylamide grafted modified PET.
[0041] Preparation of Polyacrylamide Grafted Polyethylene
[0042] Preparation Example 5
[0043] Carboxylation treatment of polyethylene: immerse the polyethylene in 0.5% sodium hydroxide acetonitrile solution, react at room temperature 25°C for 15 hours, wash with ultrapure water and dry, then immerse in 5% potassium permanganate sulfuric acid solution (sulfuric acid concentration 0.5 mol / L), react at 65°C for 1 hour, wash with ultrapure water and dry to obtain carboxylated polyethylene; add 50g of carboxylated polyethylene and 16g of polyacrylamide to 300mL of DMF solution, react at 90°C for 4 hours, remove the solvent, and dry at 60°C to obtain polyacrylamide grafted modified polyethylene.
[0044] Example
[0045] Example 1
[0046] A PE / PET sheath-core composite fiber material comprises a sheath layer and a core layer. The raw materials of the sheath layer are the following components in parts by weight: 20 parts of modified PE resin prepared in Preparation Example 1, 8 parts of a toughening agent, 1 part of an antioxidant, and 3 parts of aminosilane-modified porous silica; the raw materials of the core layer are the following components in parts by weight: 65 parts of modified PET resin prepared in Preparation Example 3 and 3 parts of diatomaceous earth; wherein the toughening agent is acrylonitrile-butadiene-styrene copolymer; and the antioxidant is hydroquinone.
[0047] The modified PE resin, toughening agent, antioxidant, etc. are mixed in proportion, stirred at a temperature of 76°C for 60 minutes, and a skin layer mixture is obtained for use; then the modified PET resin, etc. are stirred at a temperature of 85°C for 60 minutes to obtain a core layer mixture; subsequently, the skin layer mixture and the core layer mixture are added to a spinning machine respectively, melted at a temperature of 180°C for 50 minutes, co-extruded, spun, water-cooled, drawn, dried, and cut to obtain a PE / PET skin-core composite fiber material.
[0048] Example 2
[0049] A PE / PET sheath-core composite fiber material comprises a sheath layer and a core layer. The raw materials of the sheath layer are the following components in parts by weight: 40 parts of modified PE resin prepared in Preparation Example 1, 2 parts of a toughening agent, 4 parts of an antioxidant, and 9 parts of aminosilane-modified porous silica; the raw materials of the core layer are the following components in parts by weight: 30 parts of modified PET resin prepared in Preparation Example 3 and 1 part of diatomaceous earth; wherein the toughening agent is acrylonitrile-butadiene-styrene copolymer; and the antioxidant is hydroquinone.
[0050] The modified PE resin, toughening agent, antioxidant, etc. are mixed in proportion, stirred at 84°C for 55 minutes, and a skin layer mixture is obtained for use; then the modified PET resin, etc. are stirred at 95°C for 55 minutes to obtain a core layer mixture; subsequently, the skin layer mixture and the core layer mixture are added to a spinning machine respectively, melted at 180°C for 50 minutes, co-extruded, spun, water-cooled, drawn, dried, and cut to obtain a PE / PET skin-core composite fiber material.
[0051] Example 3
[0052] A PE / PET sheath-core composite fiber material comprises a sheath layer and a core layer. The raw materials of the sheath layer are the following components in parts by weight: 35 parts of modified PE resin prepared in Preparation Example 1, 5 parts of a toughening agent, 3 parts of an antioxidant, and 5 parts of aminosilane-modified porous silica; the raw materials of the core layer are the following components in parts by weight: 50 parts of modified PET resin prepared in Preparation Example 3 and 2 parts of diatomaceous earth; wherein the toughening agent is acrylonitrile-butadiene-styrene copolymer; and the antioxidant is hydroquinone.
[0053] The modified PE resin, toughening agent, antioxidant, etc. are mixed in proportion, stirred at 84°C for 60 minutes, and a skin layer mixture is obtained for use; then the modified PET resin, etc. are stirred at 95°C for 55 minutes to obtain a core layer mixture; subsequently, the skin layer mixture and the core layer mixture are added to a spinning machine respectively, melted at 180°C for 50 minutes, co-extruded, spun, water-cooled, drawn, dried, and cut to obtain a PE / PET skin-core composite fiber material.
[0054] Example 4
[0055] A PE / PET sheath-core composite fiber material comprises a sheath layer and a core layer, wherein the raw materials of the sheath layer are the following components in parts by weight: 35 parts of the modified PE resin prepared in Preparation Example 1, 5 parts of a toughening agent, and 3 parts of an antioxidant; the raw materials of the core layer are the following components in parts by weight: 50 parts of the modified PET resin prepared in Preparation Example 3 and 2 parts of diatomaceous earth; wherein the toughening agent is acrylonitrile-butadiene-styrene copolymer; and the antioxidant is hydroquinone.
[0056] The modified PE resin, toughening agent, antioxidant, etc. are mixed in proportion, stirred at 84°C for 60 minutes, and a skin layer mixture is obtained for use; then the modified PET resin, etc. are stirred at 95°C for 55 minutes to obtain a core layer mixture; subsequently, the skin layer mixture and the core layer mixture are added to a spinning machine respectively, melted at 180°C for 50 minutes, co-extruded, spun, water-cooled, drawn, dried, and cut to obtain a PE / PET skin-core composite fiber material.
[0057] Example 5
[0058] A PE / PET sheath-core composite fiber material comprises a sheath layer and a core layer, wherein the raw materials of the sheath layer are the following components in parts by weight: 35 parts of modified PE resin prepared in Preparation Example 1, 5 parts of a toughening agent, 3 parts of an antioxidant, and 5 parts of aminosilane-modified porous silica; the raw materials of the core layer are 50 parts by weight of modified PET resin prepared in Preparation Example 3; wherein the toughening agent is acrylonitrile-butadiene-styrene copolymer; and the antioxidant is hydroquinone.
[0059] The modified PE resin, toughening agent, antioxidant, etc. are mixed in proportion, stirred at 84°C for 60 minutes, and a skin layer mixture is obtained for use; then the modified PET resin, etc. are stirred at 95°C for 55 minutes to obtain a core layer mixture; subsequently, the skin layer mixture and the core layer mixture are added to a spinning machine respectively, melted at 180°C for 50 minutes, co-extruded, spun, water-cooled, drawn, dried, and cut to obtain a PE / PET skin-core composite fiber material.
[0060] Example 6
[0061] A PE / PET sheath-core composite fiber material comprises a sheath layer and a core layer, wherein the raw materials of the sheath layer are the following components in parts by weight: 35 parts of modified PE resin prepared in Preparation Example 1, 5 parts of a toughening agent, 3 parts of an antioxidant, and 4 parts of aminosilane-modified porous silica; the raw materials of the core layer are the following components in parts by weight: 50 parts of modified PET resin prepared in Preparation Example 3 and 2 parts of diatomaceous earth; wherein the toughening agent is acrylonitrile-butadiene-styrene copolymer; and the antioxidant is hydroquinone.
[0062] The modified PE resin, toughening agent, antioxidant, etc. are mixed in proportion, stirred at 84°C for 60 minutes, and a skin layer mixture is obtained for use; then the modified PET resin, etc. are stirred at 95°C for 55 minutes to obtain a core layer mixture; subsequently, the skin layer mixture and the core layer mixture are added to a spinning machine respectively, melted at 180°C for 50 minutes, co-extruded, spun, water-cooled, drawn, dried, and cut to obtain a PE / PET skin-core composite fiber material.
[0063] Example 7
[0064] A PE / PET sheath-core composite fiber material comprises a sheath layer and a core layer, wherein the raw materials of the sheath layer are the following components in parts by weight: 35 parts of modified PE resin prepared in Preparation Example 1, 5 parts of a toughening agent, 3 parts of an antioxidant, and 4.5 parts of aminosilane-modified porous silica; the raw materials of the core layer are the following components in parts by weight: 50 parts of modified PET resin prepared in Preparation Example 3 and 1.5 parts of diatomaceous earth; wherein the toughening agent is acrylonitrile-butadiene-styrene copolymer; and the antioxidant is hydroquinone.
[0065] The modified PE resin, toughening agent, antioxidant, etc. are mixed in proportion, stirred at 84°C for 60 minutes, and a skin layer mixture is obtained for use; then the modified PET resin, etc. are stirred at 95°C for 55 minutes to obtain a core layer mixture; subsequently, the skin layer mixture and the core layer mixture are added to a spinning machine respectively, melted at 180°C for 50 minutes, co-extruded, spun, water-cooled, drawn, dried, and cut to obtain a PE / PET skin-core composite fiber material.
[0066] Example 8
[0067] A PE / PET sheath-core composite fiber material comprises a sheath layer and a core layer, wherein the raw materials of the sheath layer are the following components in parts by weight: 35 parts of modified PE resin prepared in Preparation Example 1, 5 parts of a toughening agent, 3 parts of an antioxidant, and 4.8 parts of aminosilane-modified porous silica; the raw materials of the core layer are the following components in parts by weight: 50 parts of modified PET resin prepared in Preparation Example 3 and 1.2 parts of diatomaceous earth; wherein the toughening agent is acrylonitrile-butadiene-styrene copolymer; and the antioxidant is hydroquinone.
[0068] The modified PE resin, toughening agent, antioxidant, etc. are mixed in proportion, stirred at 84°C for 60 minutes, and a skin layer mixture is obtained for use; then the modified PET resin, etc. are stirred at 95°C for 55 minutes to obtain a core layer mixture; subsequently, the skin layer mixture and the core layer mixture are added to a spinning machine respectively, melted at 180°C for 50 minutes, co-extruded, spun, water-cooled, drawn, dried, and cut to obtain a PE / PET skin-core composite fiber material.
[0069] Example 9
[0070] A PE / PET sheath-core composite fiber material comprises a sheath layer and a core layer, wherein the raw materials of the sheath layer are the following components in parts by weight: 35 parts of the modified PE resin prepared in Preparation Example 2, 5 parts of a toughening agent, 3 parts of an antioxidant, and 5 parts of aminosilane-modified porous silica; the raw materials of the core layer are the following components in parts by weight: 50 parts of the modified PET resin prepared in Preparation Example 4 and 2 parts of diatomaceous earth; wherein the toughening agent is acrylonitrile-butadiene-styrene copolymer; and the antioxidant is hydroquinone.
[0071] The modified PE resin, toughening agent, antioxidant, etc. are mixed in proportion, stirred at 84°C for 60 minutes, and a skin layer mixture is obtained for use; then the modified PET resin, etc. are stirred at 95°C for 55 minutes to obtain a core layer mixture; subsequently, the skin layer mixture and the core layer mixture are added to a spinning machine respectively, melted at 180°C for 50 minutes, co-extruded, spun, water-cooled, drawn, dried, and cut to obtain a PE / PET skin-core composite fiber material.
[0072] Example 10
[0073] A PE / PET sheath-core composite fiber material comprises a sheath layer and a core layer, wherein the raw materials of the sheath layer are the following components in parts by weight: 35 parts of the modified PE resin prepared in Preparation Example 5, 5 parts of a toughening agent, 3 parts of an antioxidant, and 5 parts of aminosilane-modified porous silica; the raw materials of the core layer are the following components in parts by weight: 50 parts of the modified PET resin prepared in Preparation Example 3 and 2 parts of diatomaceous earth; wherein the toughening agent is acrylonitrile-butadiene-styrene copolymer; and the antioxidant is hydroquinone.
[0074] The modified PE resin, toughening agent, antioxidant, etc. are mixed in proportion, stirred at 84°C for 60 minutes, and a skin layer mixture is obtained for use; then the modified PET resin, etc. are stirred at 95°C for 55 minutes to obtain a core layer mixture; subsequently, the skin layer mixture and the core layer mixture are added to a spinning machine respectively, melted at 180°C for 50 minutes, co-extruded, spun, water-cooled, drawn, dried, and cut to obtain a PE / PET skin-core composite fiber material.
[0075] Comparative Example
[0076] Comparative Example 1
[0077] A PE / PET sheath-core composite fiber material comprises a sheath layer and a core layer, wherein the raw materials of the sheath layer are the following components in parts by weight: 35 parts of PE resin, 5 parts of a toughening agent, 3 parts of an antioxidant, and 5 parts of aminosilane-modified porous silica; the raw materials of the core layer are the following components in parts by weight: 50 parts of a modified PET resin obtained in Preparation Example 4 and 2 parts of diatomaceous earth; wherein the toughening agent is an acrylonitrile-butadiene-styrene copolymer; and the antioxidant is hydroquinone.
[0078] PE resin, toughening agent, antioxidant, etc. are mixed in proportion, stirred at 84°C for 60 minutes to obtain a skin layer mixture for use; then modified PET resin, etc. are stirred at 95°C for 55 minutes to obtain a core layer mixture; subsequently, the skin layer mixture and the core layer mixture are added to a spinning machine respectively, melted at 180°C for 50 minutes, co-extruded, spun, water-cooled, drawn, dried, and cut to obtain a PE / PET skin-core composite fiber material.
[0079] Comparative Example 2
[0080] A PE / PET sheath-core composite fiber material comprises a sheath layer and a core layer. The raw materials of the sheath layer are the following components in parts by weight: 35 parts of modified PE resin obtained in Preparation Example 2, 5 parts of a toughening agent, 3 parts of an antioxidant, and 5 parts of aminosilane-modified porous silica; the raw materials of the core layer are the following components in parts by weight: 50 parts of PET resin and 2 parts of diatomaceous earth; wherein the toughening agent is acrylonitrile-butadiene-styrene copolymer; and the antioxidant is hydroquinone.
[0081] The modified PE resin, toughening agent, antioxidant, etc. are mixed in proportion, stirred at 84°C for 60 minutes to obtain a skin layer mixture for use; then the PET resin, etc. are stirred at 95°C for 55 minutes to obtain a core layer mixture; subsequently, the skin layer mixture and the core layer mixture are added to a spinning machine respectively, melted at 180°C for 50 minutes, co-extruded, spun, water-cooled, drawn, dried, and cut to obtain a PE / PET skin-core composite fiber material.
[0082] Comparative Example 3
[0083] A PE / PET sheath-core composite fiber material comprises a sheath layer and a core layer. The raw materials of the sheath layer are the following components in parts by weight: 35 parts of PE resin, 5 parts of a toughening agent, 3 parts of an antioxidant, and 5 parts of aminosilane-modified porous silica; the raw materials of the core layer are the following components in parts by weight: 50 parts of PET resin and 2 parts of diatomaceous earth; wherein the toughening agent is acrylonitrile-butadiene-styrene copolymer; and the antioxidant is hydroquinone.
[0084] The modified PE resin, toughening agent, antioxidant, etc. are mixed in proportion, stirred at 84°C for 60 minutes, and a skin layer mixture is obtained for use; then the modified PET resin, etc. are stirred at 95°C for 55 minutes to obtain a core layer mixture; subsequently, the skin layer mixture and the core layer mixture are added to a spinning machine respectively, melted at 180°C for 50 minutes, co-extruded, spun, water-cooled, drawn, dried, and cut to obtain a PE / PET skin-core composite fiber material.
[0085] Performance Testing
[0086] The performance test of a PE / PET composite fiber material prepared in the embodiment and comparative example was carried out by the following method:
[0087] a. Mechanical properties test: According to GB / T 14337-2008 Chemical Fibers: Test Method for Tensile Properties of Staple Fibers, the average strength of the composite fibers of each embodiment and comparative example was tested;
[0088] b. Hygroscopicity test: Tested according to the national standard GB / T21655.1-2008, the method for evaluating the moisture absorption and quick-drying property of textiles;
[0089] c. Breathability: The water-locking and breathability performance of the composite fiber material under a pressure of 1.80 MPa; the comparison results are shown in Table 1 below:
[0090] Table 1 Performance test results
[0091]
[0092]
[0093] It can be seen from Table 1 that the performance tests of the PE / PET composite fiber materials obtained in the above embodiments all meet the quality improvement requirements of nonwoven fabrics.
[0094] Compared with Comparative Examples 1-3 and Example 3, it can be seen that the mechanical strength, hygroscopicity and air permeability of the PE / PET composite fiber material prepared in Example 2 are better than those of Comparative Examples 1-3. After analysis, it is believed that by grafting polyethylene modified by terminal amino polyether as the main raw material of the cortex, and grafting PET by polyacrylamide as the main raw material of the core layer, more hydrophilic groups are embedded in the PE macromolecules. Terminal amino polyether is an amine compound with a polyether structure, which has certain water solubility and hydrophilicity, and the polyacrylamide molecular chain contains amide groups and amino groups, which makes the modified PET resin very hydrophilic. The modification is performed at the same time so that both the cortex and the core layer have good hygroscopic effects. Both modification methods introduce amino groups and amide bonds into the fiber resin, so that similar structures exist in the resin structure, the interface compatibility of the cortex and the core layer is improved, the strength of the composite fiber is improved, and good mechanical strength is achieved. In addition, different hydrophilic grafting modification methods achieve different hygroscopic capacities of the skin-core structure, and there is a hygroscopic difference, which can further accelerate the hygroscopicity and moisture conduction of the fiber, and improve the quick-drying effect of the non-woven fabric.
[0095] By comparing Example 3 with Examples 6-8, it can be seen that the mechanical strength, hygroscopicity and air permeability and other performance indicators of the PE / PET composite fiber material prepared in Example 7 are better than those of the compared examples. It is analyzed that the hygroscopic effect of the cortex and the core layer, the moisture conduction function and the certain water storage capacity of the core layer are used to jointly improve the hygroscopicity, air permeability and quick-drying effects of the fiber. This may be because when the mass ratio of the aminosilane-modified porous silica in the cortex and the hygroscopic filler in the core layer is 3:1, the adjustment of the contents of the two achieves a better synergy of hygroscopicity, moisture conduction and water storage, so that the fiber can achieve the best quick-drying effect.
[0096] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.
Claims
1. A PE / PET sheath-core composite fiber material, characterized in that: The invention comprises a skin layer and a core layer. The skin layer raw material comprises the following components in parts by weight: 20-40 parts of modified PE resin, 2-8 parts of toughening agent, and 1-4 parts of antioxidant; the core layer raw material comprises the following components in parts by weight: 30-65 parts of modified PET resin; wherein the modified PE resin is amino-terminated polyether grafted polyethylene; and the modified PET resin is polyacrylamide grafted PET.
2. The PE / PET core-skin composite fiber material according to claim 1, characterized in that: The skin layer raw material also includes 3-9 parts of aminosilane modified porous silica.
3. The PE / PET core-skin composite fiber material according to claim 1, characterized in that: The preparation of amino-terminated polyether grafted polyethylene includes the following steps: plasma treating polyethylene; adding the treated polyethylene and amino-terminated polyether into DMF solution, reacting at 90-95°C for 2-4h, removing the solvent and drying to obtain amino-terminated polyether grafted polyethylene.
4. The PE / PET core-skin composite fiber material according to claim 2, characterized in that: The core layer material also includes 1-3 parts of hygroscopic filler.
5. The PE / PET core-skin composite fiber material according to claim 4, characterized in that: The hygroscopic filler is one or more of diatomaceous earth, sepiolite and perlite.
6. The PE / PET core-skin composite fiber material according to claim 1, characterized in that: The preparation of the polyacrylamide grafted PET comprises the following steps: carboxylation treatment of PET resin; adding the carboxylated PET resin and polyacrylamide into DMF solution, reacting at 85-95° C. for 2-4 hours, removing the solvent, and drying to obtain the polyacrylamide grafted modified PET.
7. The PE / PET core-skin composite fiber material according to claim 4, characterized in that: The mass ratio of the aminosilane-modified porous silica to the hygroscopic filler is 3:
1.
8. The PE / PET core-skin composite fiber material according to claim 1, characterized in that: The toughening agent is acrylonitrile-butadiene-styrene copolymer; the antioxidant is hydroquinone.
9. The method for preparing a PE / PET core-skin composite fiber material according to claim 1, characterized in that: The steps include: The modified PE resin, toughening agent and antioxidant are mixed in proportion, stirred at a temperature of 76-84°C for 55-60 minutes to obtain a skin layer mixture for use; the modified PET resin is then stirred at a temperature of 85-95°C for 55-60 minutes to obtain a core layer mixture; subsequently, the skin layer mixture and the core layer mixture are respectively added to a spinning machine, melted, co-extruded, spun, water-cooled, drawn, dried, and cut to obtain a PE / PET skin-core composite fiber material.
10. The method for preparing a PE / PET core-skin composite fiber material according to claim 9, characterized in that: The skin layer mixture also includes aminosilane-modified porous silica, and the core layer mixture also includes a hygroscopic filler.
11. The method for preparing a PE / PET core-skin composite fiber material according to claim 9, characterized in that: The melting temperature is 176-190° C., and the melting time is 50-60 minutes.
Citation Information
Patent Citations
Plant extract modified ES (ethylene-propylene side by side) composite fiber and preparation method thereof
CN109797455A
Plant dyeing method for modified degradable polyester
CN115897267A